Furfurylation of tropical wood species with and without silver nanoparticles: Part II: Evaluation of wood properties. Issue 1 (2nd January 2023) - Gaitán-Alvarez, Johanna; Berrocal, Alexander; Lykidis, Charalampos; Moya, Roger; Mantanis, George I.
ABSTRACT: The purpose of the work was to assess the combined effect of furfurylation, along with the addition of silver nanoparticles (NPsAg), on the thermal stability, density, water absorption, hardness and biological durability of juvenile tropical woods originating from Costa Rican forest plantations. It was demonstrated that the weight percentage gain (WPG) of wood treated with furfuryl alcohol (FA) varied from 14.44% to 44.26%, and from 12.92% to 44.52% after the addition of NPsAg. Additionally, for species with WPG over 25%, thermal stability as well as durability was greater, while water absorption was lower, compared to species with lower WPGs. Improvement of hardness was only achieved with WPG values over 35%; therefore, only species of high permeability ( V. ferruginea, V. guatemalensis, C. odorata, S. saman and E. cyclocarpum ) showed improvement regarding this property. The addition of NPsAg induced the same behaviour as when using plain FA treatment, however, regarding wood durability, the addition of NPsAg was effective only for species with WPG under 20%.